የመኖ ዘር አመራረትና አያያዝ - Adie, Aberra; Bezabih, Melkamu; Mekonnen, Kindu; Assefa, Getnet; Gebreyes, Million (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Training Workshop on Climate Smart Livestock Feed and Forage Innovations-Amharic